2019
DOI: 10.1136/vr.104917
|View full text |Cite
|
Sign up to set email alerts
|

Home monitoring of heart rate and heart rhythm with a smartphone‐based ECG in dogs

Abstract: The feasibility of the home monitoring of heart rate (HR) and rhythm through ECG tracings recorded by owners with a smartphone ECG device was evaluated in dogs. Smartphone ECG tracings were recorded by owners at home using a single-lead ECG device and sent via email for interpretation. A questionnaire was prepared to assess the owner’s opinion regarding this home monitoring service. Recordings were evaluated by two operators, and agreement was evaluated for HR and rhythm diagnosis. Thirty-three dogs were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
(58 reference statements)
1
22
1
Order By: Relevance
“…In a study of horses, 48/50 smartphone ECGs were of diagnostic quality ( 6 ), this was similar to our study, with the exception of the 3 does where PR intervals were not determined. Studies of horses and dogs have found perfect heart rate agreement with smart-phone based ECGs ( 4 , 6 , 13 ), and while the BA heart rate agreement in the does of this study was not perfect, it was close enough that differences may be clinically insignificant (113.5 ± 10.6 vs. 115 ± 10.9 bpm). In cattle smartphone ECGs were found to be reliable indicators of heart rate and some ECG parameters ( 7 ), and this appears to be in agreement with the findings of the does in the study.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In a study of horses, 48/50 smartphone ECGs were of diagnostic quality ( 6 ), this was similar to our study, with the exception of the 3 does where PR intervals were not determined. Studies of horses and dogs have found perfect heart rate agreement with smart-phone based ECGs ( 4 , 6 , 13 ), and while the BA heart rate agreement in the does of this study was not perfect, it was close enough that differences may be clinically insignificant (113.5 ± 10.6 vs. 115 ± 10.9 bpm). In cattle smartphone ECGs were found to be reliable indicators of heart rate and some ECG parameters ( 7 ), and this appears to be in agreement with the findings of the does in the study.…”
Section: Discussioncontrasting
confidence: 51%
“…The ECGs collected during this study were collected from skin that had been prepared with alcohol for improved contact. This technique has been described for dairy cattle ( 7 ) as well as dogs ( 13 ). Practitioners should be aware that other techniques for improving skin contact have been described, such as the use of ultrasound gel or clipping of the skin ( 3 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 8 A study evaluated the feasibility of heart rate and rhythm home monitoring with an sECG device in healthy and cardiopathic dogs. 9 Moreover, the device was used to detect prerace and postrace heart rate and rhythm in Thoroughbred horses that received furosemide 10 and as a rapid screening for cardiac arrhythmias in draft horse' competition. 11 Another study evaluated the use of smartphone device to obtain ECG data in seven horses while they were standing, walking and trotting.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we only used a maximum of hours of ECG recording to assess the accuracy of shorter duration ECG recordings. To the authors knowledge, currently available at-home tools for continuous, short duration ECG evaluation (including smartphone-based ECG platforms, event recorders or continuous loop recorders) do not have the capacity to record continuous ECG for more than one-hour duration [ 13 , 16 ]. Therefore, at the time of publication, practically any continuous ECG recording duration longer than one hour may not be practically feasible without placement of a version of Holter monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, methods of HR estimation based on pulse detection or peripheral rate of blood flow are unlikely to be accurate given the frequent nature of pulse deficits in dogs with AF and requires further investigation. ECG based devices such as a smartphone-based ECG (AliveCor®, AliveCor® Inc., San Francisco, California) has been previously evaluated in dogs with AF and was noted to have good owner compliance in using these devices for short duration ECG recording [ 13 ]. While AliveCor smart phone ECG provided good rhythm evaluation in dogs, there were considerable differences between veterinary cardiologists for estimation of HR using AliveCor obtained ECG in dogs with both sinus rhythm and AF [ 13 ].…”
Section: Introductionmentioning
confidence: 99%